Study on laser perforated films as gas permeable packaging for confused flour beetle (Tribolium confusum Jacquelin du Val.) control inside food packaging. (January 2015) - Nateq Golestan, Mohammad; Ghosta, Youbert; Pourmirza, Ali Asghr; Valizadegan, Orouj
Abstract: Storage insect pests are a major threat for packaged foodstuffs and most packages have low permeability to the fumigant gases used for control. In this study, the effects of O3 gas concentrations (50, 100, 150 ppm) in the atmosphere of 70% CO2 on adults of Confused flour beetle placed inside three foodstuffs including; wheat (alive), wheat flour and rolled oats (inanimate) packed with laser perforated BOPP film with 80 μ width, were evaluated. The experiments performed at 25 ± 2 °C and 35 ± 5% r.h. with exposure period seven days. The results showed that the regression models between permeability index (PI) of Bopp film and insect mortality in three different foodstuffs and also empty packages were different. Regression model for packaged wheat was quadratic, for wheat flour and rolled oats was power and in empty packages, linear model was fitted with 95% confidence. The additive effect between O3 and CO2 gases on pest mortality placed in empty non-perforated film was found. Other results proved that the mean mortality in three products in the same condition is different and highest mortality was observed in wheat. Also, the interactions observed between factors at 0.05 level. Present study suggests laser perforated BOPP films as a proper packaging for inanimate products and non-perforated BOPP films for live products. Highlights: We offer a new model according to MAs called Gas-permeable Packaging (GPP). The treatment of O3 + CO2 mixture has additive effect on mortality in packages without foodstuffs with 95% confidence. The relationship between mortality rate and permeability index of films in foodstuffs treatment were fitted Non-linear models. We observe two interactions between Foodstuffs, permeability index and Ozone concentration treatments at 0.05 level.